Biochemistry. - Zubay, Geoffrey L.; Zubay ([S.l.] : William C. Brown, 1993)
Provides the context for discussing several unique functions and the corresponding properties of the proteins. A revision of thermodynamics, examples of representative enzymes that utilize each other, and coverage of lipid bilayers which provide a solid foundation for understanding biological membrane phenomena are featured in this biochemistry book.
Keywords: biochemistry